1998
DOI: 10.1021/ja972265s
|View full text |Cite
|
Sign up to set email alerts
|

Co- and Counterrotation of Magnetic Axes and Axial Ligands in Low-Spin Ferriheme Systems

Abstract: The orientation of the principal axes of the g tensor with respect to the relationship of axial ligand planes to the porphyrin nitrogens has been studied in the framework of the one-electron crystal field model for tetragonal and rhombic low-spin d5 complexes such as ferriheme centers. All five d atomic orbitals were taken into account for two different ground-state electronic configurations, the “normal” (d xy )2(d xz ,d yz )3 and the “novel” (d xz ,d yz )4(d xy )1 configurations. The expressions for the g te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
107
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 62 publications
14
107
0
Order By: Relevance
“…This can only be the case when the two Fe-His bonds have a comparable strength [34,35]. This assignment is also corroborated by the fact that only one set of cross peaks between the double quantum (DQ) nuclear frequencies is found for the coordinating N ε of the two axially binding histidines (Figures 2a-b, 3a-b).…”
Section: Continuous-wave Electron Paramagnetic Resonance (Cw Epr) Cwmentioning
confidence: 55%
“…This can only be the case when the two Fe-His bonds have a comparable strength [34,35]. This assignment is also corroborated by the fact that only one set of cross peaks between the double quantum (DQ) nuclear frequencies is found for the coordinating N ε of the two axially binding histidines (Figures 2a-b, 3a-b).…”
Section: Continuous-wave Electron Paramagnetic Resonance (Cw Epr) Cwmentioning
confidence: 55%
“…The re-evaluation of the x-ray diffraction data to reconcile the alternate heme orientation in the crystal and solution has shown that the heme in the crystal is, in fact, rotated by 180°about the ␣,␥-meso axis from that originally reported (8) 4 and the same as found by 1 H NMR in solution. Theoretical considerations (61,64) confirmed in model compounds (65,66) dictate that if the orbital ground state is determined by the axial His(F8) bonding, the rhombic axes, , and the angle between the heme N-Fe-N and imidazole plane, (Fig. 1C), obey the counter-rotation rule where ϭ Ϫ.…”
Section: Discussionmentioning
confidence: 85%
“…62 These angle plots are based on the contact shifts that measure the calculated spin density distributions in the e(π) orbital of the ferriheme for which the nodal plane of that orbital is coincident with the nodal plane of the axial ligand(s), 62 and the calculated pseudocontact shifts that depend on the orientation of the magnetic axes of the heme, with counter-rotation of ligand and x or y axes. 63 Table 1, and are compared to the orientation of the effective nodal plane of the histidine imidazole and the A:B ratios as determined by NMR spectroscopy in this work. The latter, and their relationship to the X-ray crystallographic data, are discussed below.…”
Section: Resultsmentioning
confidence: 99%